Smart water filter / Abu Hanifah Ab Hamid ... [et al.] - Ab Hamid, Abu Hanifah; Yusoff, Zaidi; Juhari, Mohd Hanif (Universiti Teknologi MARA, Kedah, 2018)
Lifesaving is defined as something that saves a person's life; something or someone which pro-vides help that is badly needed. A life saver product could provide emergency relief or guidelines to save someone's life, or to help a person in reviv-ing themselves. Nowadays, people commonly hear through the mass media about the issue on lost hikers in the forest. In that situation, instead of relying on a water pack for survival, the victim also needs to rely on nutrition sources found in the forest. In general, a human body can only survive for three days without water. However, during that period of time, the victim is already exposed to dehydration. Water sources could easily be found depend-ing on the area of forest. Normally water source can be found from the river, if not the victim can extract water from plants such as bamboo, moss and pitcher plant. Bamboo trees are easier to find in the forest, but to extract the water from the bamboo plant, one needs to clean cut between the stems. But still the victim needs a filter to purify the extracted water and to ensure that it is safe to drink. Hence, with this Smart Water Filter, the victim can extract and filter the water from the bamboo and at the same time, the victim could also extract water from others sources such as rivers and puddles.